Solid Cystic Pseudo Papillary Tumor of the Pancreas (Gruber - Frantz): A Case Report and a Review of the Literature - Wissam El Hajj Moussa; Elie Aoude; Lea Azar; Elsa Sfeir; Elie Chelala (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2018)
Background: Solid cystic pseudopapillary tumor of the pancreas (SCPTP), commonly known as Gruber-Frantz's tumor is a rare form of pancreatic tumors commonly misdiagnosed as pancreatic pseudocysts. It mainly affects middle-aged women, with an excellent prognosis. Different techniques are used to diagnose this type of tumor, while surgery remains the mainstay of the treatment.  Purpose: Our aim is to increase awareness of such pancreatic tumors in young females, by highlighting surgical resection as the treatment of choice, and its possibility of recurrence which necessitates further guidelines for follow-up. Case presentation: A 50-year old woman presented with vague abdominal pain and bloating for 1 month. An abdominal CT-scan depicted a hypo dense 5 cm mass in the tail of the pancreas enhancing solid content and some calcifications. A total body and selective hepatic MRI confirmed the findings. Only serum cancer antigen (CA19-9) was elevated at 41ng/dl. A tentative CT-guided trans-gastric fine needle aspiration (FNA) of the pancreas revealed no pancreatic tissue. The patient underwent an extended curative R0 distal splenopancreatectomy. The pathology revealed a completely resected well-differentiated endocrine tumor without lymph node involvement. An immunohistochemistry study was positive for CD-56, Vimentine, CD10, and Ki-67 antigen with low mitotic index (0-1%). Post-operative course was uneventful and patient was discharged at day 6 post-op.  Discussion: SCPTP is a rare entity, currently reported in literature as a low malignant potential tumor, affecting mainly middle-aged women. Body and tail are most commonly affected. CT-scan or MRI are used to diagnose and classify SCPTP, however, incisional biopsy often provides the correct diagnosis. Surgery remains the definitive best curative treatment of SCPTP regardless of the size of the tumor, and prognosis is excellent following resection. Recurrence rate has been reported up to 8.3%, potentiating routine imaging control. Current and future studies aim to investigate metabolic and genetic characteristics of this type of tumor.